2002
DOI: 10.1139/y02-021
|View full text |Cite
|
Sign up to set email alerts
|

ACEH/ACE2 is a novel mammalian metallocarboxypeptidase and a homologue of angiotensin-converting enzyme insensitive to ACE inhibitors

Abstract: A human zinc metalloprotease (termed ACEH or ACE2) with considerable homology to angiotensin-converting enzyme (ACE) (EC 3.4.15.1) has been identified and subsequently cloned and functionally expressed. The translated protein contains an N-terminal signal sequence, a single catalytic domain with zinc-binding motif (HEMGH), a transmembrane region, and a small C-terminal cytosolic domain. Unlike somatic ACE, ACEH functions as a carboxypeptidase when acting on angiotensin I and angiotensin II or other peptide sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
129
2
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(136 citation statements)
references
References 40 publications
2
129
2
3
Order By: Relevance
“…Previous studies have demonstrated moderate ACE2 expression in the lungs of both humans (28) and mice (29), with high levels of ACE2 in the kidney, heart, testis, and small intestine of both species (29)(30)(31). In the human lung, immunostaining found that ACE2 was localized to endothelial and smooth muscle cells of large and small blood vessels, as well as type I and II alveolar epithelial cells and bronchial epithelial cells (32,33).…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have demonstrated moderate ACE2 expression in the lungs of both humans (28) and mice (29), with high levels of ACE2 in the kidney, heart, testis, and small intestine of both species (29)(30)(31). In the human lung, immunostaining found that ACE2 was localized to endothelial and smooth muscle cells of large and small blood vessels, as well as type I and II alveolar epithelial cells and bronchial epithelial cells (32,33).…”
Section: Discussionmentioning
confidence: 93%
“…16 Ten years elapsed before the independent discovery of ACE2 provided a more complete understanding of the biochemical physiology of the enzymes involved in the formation of angiotensin peptides. 17,18 A thorough analysis of the biological actions of Ang-(1-7) is outside the scope of this presentation; several review articles have rigorously examined the evidence. 19 -22 Suffice it to say that the actions of Ang-(1-7) are composed of both activation of peripheral vasodilator mechanisms and antitrophic effects mediated by inhibition of protein synthesis.…”
Section: Formation and Functions Of Ang-(1-7)mentioning
confidence: 99%
“…4 ACE2 is a membrane-bound enzyme that acts as a monocarboxypeptidase and is an essential regulator of heart function. 5 However, ACE2 is not inhibited by the classical ACE inhibitors captopril and lisinopril, 1,6 which are used as antihypertensive drugs. Within the RAS, ACE2 competes with ACE because it is capable of hydrolyzing the inactive decapeptide angiotensin I (Ang I) into the nonapeptide Ang(1-9), thus decreasing the amount of Ang I available for pressor Ang II generation by ACE.…”
mentioning
confidence: 99%